(untitled) (Research, Society and Development, 2025)
The present study aimed to report the experience of two street runners, one amateur and one professional athlete, highlighting the impacts of sports practice on their routines, health, and quality of life. This is a descriptive, qualitative study in the form of an experience report, developed through direct observation and participants’ personal accounts. The analysis revealed that street running significantly contributed to health promotion and physical conditioning, in addition to improving self-esteem, discipline, and overall well-being. Furthermore, in the context of the professional athlete, running proved to be an essential tool for sports performance and the achievement of competitive goals. For the amateur runner, the practice was perceived as accessible and democratic, fostering socialization, pleasure, and improvements in quality of life. It is concluded that street running, regardless of the level of engagement, represents a relevant strategy for health care and personal development, although professional support is recommended to maximize benefits and reduce associated risks.